9x-(-6x-6)=-24

Simple and best practice solution for 9x-(-6x-6)=-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-(-6x-6)=-24 equation:


Simplifying
9x + -1(-6x + -6) = -24

Reorder the terms:
9x + -1(-6 + -6x) = -24
9x + (-6 * -1 + -6x * -1) = -24
9x + (6 + 6x) = -24

Reorder the terms:
6 + 9x + 6x = -24

Combine like terms: 9x + 6x = 15x
6 + 15x = -24

Solving
6 + 15x = -24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 15x = -24 + -6

Combine like terms: 6 + -6 = 0
0 + 15x = -24 + -6
15x = -24 + -6

Combine like terms: -24 + -6 = -30
15x = -30

Divide each side by '15'.
x = -2

Simplifying
x = -2

See similar equations:

| -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 | | 2x+4x-8=34 | | 8y+10=16-8y | | 10x-7=3x+5 | | 15-5(3-8y)= | | -7(1+5x)+3=-8(4x+5) | | y=6sin(6x) | | 9(a-3)+2= | | 3.5x-20=2.4x-13 | | -x-x^2=14 | | 2x+4y=76 | | -7x+1=-12x-12 | | -5(1-5k)+5(-8k-2)=-4k-8k | | 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= | | 6a-17=4a+1 | | -7(2n-6)=7(n+3) | | 8=z-7 | | 3+9z-8h= | | 7x-8=3(x+2) | | 15x-9x=48 | | 8b-a=-3 | | 4(3d-2)=32 | | x^2+2x-52=0 | | -6(5+3x)=14 | | cos(6x)=cos(4x) | | 14.2=0.4(20m-7.8) |

Equations solver categories